TATA RUANG ETNIS DAN PROFESI DALAM KOTA BATAVIA (ABAD XVII - XVIII) - Novita, Aryandini; Mahmud, M. Irfan (Berkala Arkeologi, 1999)
The settlement of ethnic groups in Batavia was determined apart from the environment that supported the profession, as well as matters of race and religion as well as effectiveness in mobility. For example, ethnic groups who work as traders are placed or live near the commercial area. Groups that work as administrative staff are placed in the downtown area, which is the central government area, while groups that work in the agricultural and plantation sectors as well as groups deemed to have the potential to pose a security threat are placed in suburban areas.